Uroflowmetric changes, success rate and complications following Tension-free Vaginal Tape Obturator (TVT-O) operation in obese females. (July 2017) - Fouad, Reham; El-Faissal, Yahia M.; Hashem, Ahmed T.; Gad Allah, Sherine H.
Abstract: Objective: The goal of this study was to evaluate the outcome ofTension-free Vaginal Tape Obturator (TVT-O) operation in the treatment of urodynamic stress incontinence (USI) in obese females, with respect to uroflowmetric changes, success rate and postoperative complications. Methods: This prospective observational study included 26 patients with USI at the Obstetrics & Gynecology department-Cairo University hospital during the year 2015. The participants had body mass index (BMI) ≥ 30. Patients underwent TVT-O operation. Follow up of the patients was performed by cough test and uroflowmetry after one week, one month, three months and six months. Postoperative complications such as groin pain, sense of incomplete emptying, need to strain to complete micturition and urinary tract infection were recorded. Comparisons between groups were done using Chi square, Phi-Cramer test for categorical variables. Results: The mean age for the subjects was 43.58 ± 9.01 years. The mean BMI was 33.4 ± 2.1. The success rate of TVT-O operation was 21 out of 26 patients (≈81%). Normal maximum flow rate was in 88% of patients at week one and was normal in 100% of patients at months three and six (p = 0.101 & 0.101). Postoperative groin pain was the main complaint during the first week after operation and decreased significantly from week one to the 1st month postoperative (84.62% & 65.38%, P = 0.041). Conclusion: TVT-O operation showed a high success rate in treatment of USI in obese patients without affecting the voiding function of the bladder as proven by the uroflowmetry. The main postoperative complaint was the groin pain which significantly improved after one month.